2018
DOI: 10.1016/j.drugalcdep.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

HIV treatment optimism and crystal methamphetamine use and initiation among HIV-negative men who have sex with men in Vancouver, Canada: A longitudinal analysis

Abstract: Among HIV-negative MSM in Vancouver, HIV treatment optimism does not appear to be independently associated with CM use or initiation of use, though use of CM was both prevalent and stable over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Cognitive Escape. The findings of this model further support research showing that a greater propensity to use substances as a means to cognitively escape thinking about HIV-related risks and norms in sexual contexts (i.e., cognitive escape/escape motives) is associated with an increased odds of methamphetamine use in the past six months (Colyer et al, 2018(Colyer et al, , 2020Semple et al, 2006). The results of the present study extend these findings by showing that higher psychological distress is associated with greater escape motives, which, in turn, is associated with a greater likelihood of methamphetamine use in the past six months among both GBM living with HIV and HIV negative GBM.…”
Section: Psychological Distress Sexual Compulsivity Cognitive Escape ...supporting
confidence: 76%
See 1 more Smart Citation
“…Cognitive Escape. The findings of this model further support research showing that a greater propensity to use substances as a means to cognitively escape thinking about HIV-related risks and norms in sexual contexts (i.e., cognitive escape/escape motives) is associated with an increased odds of methamphetamine use in the past six months (Colyer et al, 2018(Colyer et al, , 2020Semple et al, 2006). The results of the present study extend these findings by showing that higher psychological distress is associated with greater escape motives, which, in turn, is associated with a greater likelihood of methamphetamine use in the past six months among both GBM living with HIV and HIV negative GBM.…”
Section: Psychological Distress Sexual Compulsivity Cognitive Escape ...supporting
confidence: 76%
“…Cognitive escape theory and the associated Escape Motives Scale were originally conceptualized by colleagues (1996, 2001) as a measure of one's motivation to use substances as a means to cognitively avoid thinking about personal HIV risk within sexual settings to more freely enjoy sex. Cognitive escape has consistently been found to positively correlate with methamphetamine use among Vancouver GBM Card et al, 2019;Colyer et al, 2018Colyer et al, , 2020. However, recent findings suggest that the Escape Motives Scale may also measure an individual's motivation to use drugs as a means to cognitively escape from more general experiences of stress (Card et al, 2019).…”
Section: Cognitive Escape Theorymentioning
confidence: 99%
“…Moreover, Sin et al [39] reported that engaging in male sex work in Malaysia was a motivating factor in the initiation of methamphetamine use. Several other studies [4042] have reported that young men who engaged in commercial sex work in a large city tended to initiate methamphetamine use.…”
Section: Discussionmentioning
confidence: 99%
“…Further, substance use has been associated with higher risk sexual behaviors (Benotsch, Kalichman, & Kelly 1999;Colfax et al 2001;Halkitis & Parsons, 2003;Rich et al, 2016;Stall et al, 2002), including condomless anal sex, which may contribute to transmission and acquisition of HIV and other sexually transmitted infections (STIs) given high prevalence rates among gbMSM Mullens et al 2009;Smith et al 2004;Frye et al 2010). Among substance-using gbMSM, prevalence of HIV and STIs are higher than among non-substance-using gbMSM (Ackers et al 2012;Chesney, Barrett, & Stall, 1998;Koblin et al, 2006;Reback & Fletcher, 2014) and consequently, substance use among gbMSM has become a more significant public health priority in Canada (Colyer et al, 2018;Knight, 2018;Lewis & Wilson, 2017). Since substance use behaviors are complex in nature, they cannot be assumed as monolithic across different social settings (Melendez-Torres & Bourne, 2016).…”
Section: Introductionmentioning
confidence: 99%